Shouldering the load yet again: Black women's experiences of stress during COVID-19 - Jolaade Kalinowski; Heather Wurtz; Madeline Baird; Sarah S. Willen (Elsevier, 2022)
Black women in the United States experience considerable amounts of stress, which has been exacerbated by the COVID-19 pandemic. Prior studies have linked stress to adverse mental and physical outcomes for Black women and, moreover, shown that Black women are more susceptible to maladaptive coping, which compounds these risks. Research on the Superwoman Schema and Sojourner's Syndrome, for instance, shows how Black women are compelled to portray strength and resilience while suffering internally and experiencing poor health outcomes. These phenomena can be attributed to the historical expectations of Black women to be pillars of their families and sources of strength despite adversity and persistent institutional discrimination. During the COVID-19 pandemic, Black women's greater likelihood of holding "essential worker" roles has further increased their risk of both COVID-19 exposure and heightened stress. Additionally, the COVID-19 pandemic has aggravated long standing structural inequities and disparities between Black women and other racial/ethnic groups. Drawing on journal entries submitted by Black women participating in the Pandemic Journaling Project (PJP), a combined online journaling platform and interdisciplinary research study, this paper illuminates the voices of Black women during the COVID-19 pandemic. Seventy-two Black women created journal entries using the PJP platform. We analyze the stories, idioms, and feelings they recorded during a global pandemic. We identify three prominent domains of stress: work and school, caregiving, and social (dis)connectedness. In addition to exploring manifestations of stress across these domains, we, discuss some of the mental health implications of COVID-19 and explore the potential for regular journaling as a possible mode of stress management among Black women.